American teacher - Roth, Vanessa; Calegari, Nínive Clements; Eggers, Dave.; McGinn, Brian; Nguyen, Thao.; Damon, Matt.; First-Run Features (Firm) ([New York?] : First Run Features, 2011)
See the stories of four teachers in different areas of the country, revealing the frustrating realities of today's teachers, the difficulty of attracting talented new educators, and why so many of our best teachers leave the profession altogether. Can we re-value teaching and turn it into a prestigious, financially attractive, and desirable profession? With almost half of American teachers leaving the field in the next ten years, now is the time to find out.
Special features: bonus scenes; more interviews.
Camera, Daniel Gold ... [et al.] ; editor, Brian McGinn ; original music, Thao Nguyen.
Narrator: Matt Damon.
DVD format.
English subtitled for the deaf and hard of hearing; closed-captioned.
Keywords: Teachers -- United States; Teachers -- Job satisfaction -- United States; Teachers -- Salaries, etc. -- United States; Documentary films; Video recordings for the hearing impaired